ANALISIS PENGARUH NPL, CAR, ROA, LDR DAN SIZE TERHADAP CKPN (Studi Kasus pada Bank Konvensional yang Tercatat di Bursa Efek Indonesia 2010-2014 ) - Fitriana, Maretha Eka; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2015)
Loan Loss Provision (CKPN) is important in the banking because CKPN can keep banking in remain likuid. The problems on the average CKPN in commercial banks during the 2010-2014 periode, CKPN value is always decreasing, but not in accordance with the provisions stipulated by Bank Indonesia. This study aimed to examine the effect of the Non-performing Loan, Capital Adequacy Ratio, Loan to Deposit Ratio, Size and Return On Asset against the Allowance for Impairment Loss Loan Provision Conventional Bank Listed in Indonesia Stock Exchangeperiod 2010-2014 so we can know why the CKPN value can not accordance with the provisions stipulated by Bank Indonesia. The sampling technique that used in this research is purposive sampling method. The total sample in this research is 21 conventional bank. The analysis used multiple regression. The results of this study found that NPL, CAR and ROA has significant and positive impact on CKPN, while the Size variable have no significant positive effect on CKPN and LDR have no significant negative effect on CKPN. Additionally obtained adjusted R -square value of 54.5 %. This means that for 45.5 % explained by other variables outside the model.